Exploring the “Can Do” and “Will Do” factors of human capital to enhance university performance - F. Fairuzzabadi; Mohamad Shaharudin Samsurijan; Syarifah Rahmawati; Zahri Hamat; Rustam Effendi (Universitas Muhammadiyah Malang, 2024)
This study explores the